Attitude toward English among Vietnamese students in the Philippines - Berowa, Annie Mae C. (Animo Repository, 2018)
Language attitude is considered as one of the most important components in the success of learning a target language. Such argument inspired the researchers of this study to investigate the attitudes of the Vietnamese learners in the Philippines toward the English language, and to know if their attitudes are influenced by their age, gender and socio-economic status (SES). This investigation is anchored on the Socio- Educational Model espoused by Gardner in 1985 that attitude is an important motivating factor in language learning. The data was gathered through the use of questionnaire and one-on-one interviews. For the statistical tools, weighted mean was employed to find out the attitudes held by the participants toward English while Chi-square Test for Independence was utilized to determine if there is a significant relationship between the participants’ language attitude and the variables identified. The results illustrated that Vietnamese students in the Philippines have high positive attitude toward the English language. It was further discovered that there was no significant relationship between the attitudes of the participants toward the target language vis-à-vis age, gender and socioeconomic status (SES). © 2018 Asian E F L Journal Press. All Rights Reserved.